Liposomal black mulberry extract loaded-nanofibers: preparation, characterisation, and bioaccessibility of phenolics by simulated in vitro digestion combined with the Caco-2 cell model - Caglar, Nagihan Kalintas; Saroglu, Oznur; Karakas, Canan Yagmur; Tasci, Cansu Ozel; Catalkaya, Gizem; Yildirim, Rusen Metin; Gultepe, Eyup Eren; Gulec, Sukru; Sagdic, Osman; Capanoglu, Esra; Karadag, Ayse (WILEY, 2024)
Black mulberry extract (BME) is rich in phenolics; however, their health benefits are restricted by their instability and poor absorption in the small intestine. Liposomal BME-loaded pullulan/pectin nanofibers were developed to enhance the in vitro bioaccessibility of BME. The liposomes with BME (0.8%, w/v), were produced by the thin-film hydration and ultrasonication method with a size of 76.41 +/- 1.23 nm and encapsulated 79.40 +/- 0.99%.of the BME. Scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) images showed that the uniform distribution of liposomes within the defect-free fiber structure. Liposomal BME loading elevated the mucoadhesiveness of the nanofibers compared to free BME loading. Liposomal BME-loaded nanofiber demonstrated a nearly two-fold increase in the bioaccessibility of anthocyanins. The cellular release of all four different anthocyanins by Caco-2 cells was significantly higher (3.92%-10.50%) in liposomal BME-loaded nanofiber. Therefore, liposomal nanofibers show great potential as a method for delivering phenolics, specifically anthocyanins.
Keywords: Anthocyanins; electrospinning; mucoadhesion; pectin; pullulan; MORUS-NIGRA L.; ANTIOXIDANT ACTIVITY; ABSORPTION; METABOLISM; FOOD; PHARMACOKINETICS; BIOAVAILABILITY; NANOLIPOSOMES; ENCAPSULATION; Food Science & Technology